(untitled) (Journal of the College of Basic Education, 2022)
The current study dealt with the environment and the geographical distribution of species of the genus Althaea L. growing wild in Iraq, as this genus includes species that grow in Iraqi environments and forests. The study indicated that there is a diversity in the environments in which the species of the genus grow, and the species varied in their distribution over the Iraqi botanical geographic provinces and in the extent of the spread of species over the provinces. And Upper Jazira Province (FUJ) was one of the widely distributed species. While the two species A.cannabina and A.hirsuta shared their distribution in three provinces of the mountainous region, which are Sulaymaniyah, Rawanduz and Amadiya, but the latter exceeded the first in its presence in Nineveh province. (FNI) As for the type A. officinalis, its spread was limited to the mountainous region (M) in the provinces of Amadiya and Rawanduz. It was found that this type is less present and widespread than the rest of the species.These plant variations and species dispersal zones are of taxonomic interest and help in isolating species of the genus, bearing in mind that classification begins with the phenotypic characteristics that are the basis for isolating and diagnosing species.